Elastic modulus of 316 stainless steel lattice structure fabricated via binder jetting process. Issue 7 (2nd May 2016) - Tang, Y.; Zhou, Y.; Hoff, T.; Garon, M.; Zhao, Y. F.
Abstract : This study mainly evaluates the elastic modulus of 316 stainless steel lattice structures fabricated via binder jetting process. In this present research, both solid and lattice samples are designed and fabricated by binder jetting process for two different types of mechanical tests. Besides experimental study, a numerical model based on energy approach has been proposed to predict the effective elastic modulus of fabricated lattice samples. By comparing the calculated results of the proposed numerical model with the experimental results, the established model is proved to be validated. This numerical model can be used to determine the parameters of lattice structures fabricated by binder jetting process for desired mechanical properties. At the end, both advantages and disadvantages of the lattice structures fabricated by binder jetting process are analysed. Based on this analysis, the potential application and future research work are pointed out.